2014
DOI: 10.1590/1677-5449.0046
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral internal carotid artery agenesis: a case report

Abstract: Agenesis of the internal carotid artery (ICA) is defined as a congenital absence of the carotid canal and occurs in less than 0.01% of the population. This anomaly is usually diagnosed as an incidental finding or after a cerebrovascular event. We present the case of a 36-year-old woman, with bilateral agenesis of the ICA who had suffered a subarachnoid hemorrhage due to ruptured aneurysm of the basilar artery. Therefore, agenesis of the ICA is a condition that, although rare, should be considered since there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The absence of the ICA occurs in less than 0.01% of the population (4,13). In 2014, Ulger et al (14) stated that 35 cases of agenesis of the ICA had been reported in literature, while Oliveira et al (15) found only 26 cases agenesis of the ICA in literature. In the study conducted by Taşar et al (1) the prevalence of aplasia and hypoplasia of the ICA was 0.13%.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of the ICA occurs in less than 0.01% of the population (4,13). In 2014, Ulger et al (14) stated that 35 cases of agenesis of the ICA had been reported in literature, while Oliveira et al (15) found only 26 cases agenesis of the ICA in literature. In the study conducted by Taşar et al (1) the prevalence of aplasia and hypoplasia of the ICA was 0.13%.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical and hemodynamic stresses placed on the embryo along with comprising effects related to exaggerated folding of the embryo toward one side as well as constriction by amniotic bands are accounted. No explanation for bilateral absence has been rendered in the literature yet [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Padgett's has proposed that the internal carotid artery originates from the dorsal aorta and the 3rd aortic arch during the early embryonic stage, with the full development of the ICA by 6 weeks [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations